Correction to: Vilnius Declaration on chronic respiratory diseases: multisectoral care pathways embedding guided self‐management, mHealth and air pollution in chronic respiratory diseases. Issue 1 (17th November 2020) - Valiulis, Arunas; Bousquet, J.; Veryga, A.; Suprun, U.; Sergeenko, D.; Cebotari, S.; Borelli, D.; Pietikainen, S.; Banys, J.; Agache, I.; Billo, N. E.; Bush, A.; et al.
Abstract : An amendment to this paper has been published and can be accessed via the original article.